Pengaruh Gaya Hidup Konsumen Muslim Terhadap Adopsi Smartphone Apple (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Airlangga) - Indra Rahmadi; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this research is testing the influence of moslem consumer lifestyle to Apple smartphone adoption by students of Economics and Business Faculty of Airlangga University. This research uses quantitative approach and questionnaire for primary data collecting. The test was done using simple linear regression, where endogen variable (Y) is apple smartphone adoption and exogen variable (X) is moslem consumer lifestyle. Samples of this research was chosen using nonprobability sampling technique combined with accidentalsampling and purposive sampling. Samples in this research are 100 students of Economics and Business Faculty of Airlangga University.Based on the result of this research linear regression equation obtained is Y = 0.787 + 0.840 X. The measurenment of the influence of moslem consumer lifestyle to Apple smartphone adoption by students of Economics and Business Faculty of Airlangga University has 0.290 (29%) R2 value. The result of this research shows that moslem consumer lifestyle has a significant influence with Apple smartphone adoption by students of Economics and Business Faculty of Airlangga University.